ROLE OF LOW-DOSE AZITHROMYCIN IN THE MANAGEMENT OF CYSTIC BRONCHIECTASIS: A CASE SERIES - Paulus Taufik; Maulid Hidayat; Prima Bela Fathana (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2023)
Bronchiectasis is an abnormal chronic and persistent dilatation of the bronchi that is accompanied by destruction of the bronchial walls due to congenital or acquired disorders such as chronic respiratory tract infections. Recurrent respiratory tract infections are characteristic of bronchiectasis. Radiological examination plays a role in diagnosis, a thin section CT to confirm a diagnosis of bronchiectasis when clinically suspected, and provides clearer information on lung morphology. The goals of treating bronchiectasis are to prevent exacerbations, reduce complaints, improve the patient's quality of life, and stop the disease from worsening. Therapy is expected to address the proven underlying cause, cutting off the vicious cycle of bronchiectasis Long-term antibiotics are considered in patients with bronchiectasis with frequent exacerbations three or more times per year to relieve symptoms and reduce the frequency of exacerbations. Macrolides are a plausible alternative antibiotic and anti-inflammatory agent with a lower burden of treatment for bronchiectasis patients. We present three cases of Bronchiectasis that were admitted to Mataram University Hospital. The three cases were given Long-term antibiotics with low-dose Azithromycin for 2 and 3 months. This report demonstrates clinical improvement in a reduction of exacerbation frequency, improvement in quality of life, decreased sputum production, and increased ability to carry out activities in patients treated with low-dose azithromycin. The most common side effect that appears in three cases is gastrointestinal disturbances.